Interaction of Parenting Style of Mothers and Paediatric Diabetes Management - Jolanta Žilinskienė; Linas Šumskas; Dalia Antinienė; Jolita Jonynienė (Lithuanian Sports University, 2021)
Background. Parent-child relationship and parenting style are very important for the child's mental and physical health. This study was focused on investigating the association between mothers' parenting style (PS) and their children's with type I diabetes (T1DM) disease management. We hypothesized that mothers' PS interact with their children's T1DM outcomes. Methods. One hundred thirty-one mothers, the main caregivers of their diabetic children, filled in the parenting style and demographic questionnaires. The indicator of diabetes management was Haemoglobin A1c (HbA1c) - the main form of glycosylated haemoglobin. PS scales and subscales were associated with glycaemic management indices. Binary logistic regression analysis was applied for the assessment of the association between mothers' PS and their children's with T1DM disease management. Results. While logistic regression analysis did not demonstrate statistically significant interaction of T1DM management and mothers' PS scales and subscales, cluster analysis showed that in the confrontation with T1DM, the relationships between children and parents were dominated by negative elements of PS: lack of emotional warmth, support, reasoning and especially democratic participation. Conclusion. Children's T1DM management and their mothers' PS scales and subscales did not demonstrate statistically significant interaction. PS negative elements dominate in mothers' upbringing: lack of emotional warmth, support, reasoning and especially democratic participation. Keywords: type 1 diabetes, parenting skills, parenting style, diabetes management.